The impact of massive tech layoffs on victims and those who remain employed - Tira, Ligia Couto (2024)
The use of mass layoffs by companies is not a new strategy and waves of largescale workforce reductions have been carried out before in different contexts. This topic returned to the spotlight when giant technology companies announced significant cuts in their workforce. Mass layoffs result in the formation of two groups: (a) victims, who lose their jobs involuntarily, and (b) survivors, who remain with the company. The aim of this study is to understand the impact of this strategy on both groups, considering personal and professional aspects. To obtain the results, the research adopted a qualitative approach through interviews with the two groups. By analyzing the data, it was possible to understand what were the most difficult aspects for the victims and survivors, as well as some aspects that were not highly impactful for the two groups. The study aims to help companies, based on the reports of the participants, to develop better practices when communicating and conducting situations of this nature.